Microwave losses of nanostructure Li-Ni ferrites in X-band and Ku-band - Lafta, Sadeq H. (Iraqi Journal of Physics, 2019)
The molar ratio(x) of Li-Ni ferrites in the formula Li0.5-0.5xNixFe2.5-0.5xO4 was varied in range 0.1-1.0 by hydrothermal process. TheXRD, SEM, and TEM tests were conducted to examine the samplescrystalline phase and to characterize the particles shapes and sizes.The high purity spinel structure was obtained at med and high xvalues. SEM and TEM images showed the existence of differentferrite particles shapes like nanospheres and nanorods. Themaximum particle size is around (20nm). These size encourageoccurrence of super paramagnetic state. The reflection loss andinsertion loss as microwave losses of Li-Ni ferrite-epoxy compositeof 1mm thickness and mixing ratio 39.4 wt was investigated. Theminimum reflection loss in x-band and in Ku band was about -8dBaround 10GHz and lower than -18dB respectively. The insertion lossexceeded -6dB in the two band for some samples.